Categorization of Persons Deprived of Liberty (PDLs) - Pajarillo Guadamor, Maita (International Journal of Psychosocial Rehabilitation, 2020)
The DILG Act of 1990 created one of its tri-bureaus, the Bureau of Jail Management and Penology referred to as the Jail Bureau, initially consisting of officers and uniformed members of the Jail Management and Penology Service as constituted under Presidential Decree No. 765. The Bureau is in charge of supervising district, city, and municipal jails in the country. Under the Commission on Higher Education Memorandum #21 series of 2005, the policies and standards for the criminology program under CMO #21, series of 2005, include courses on institutional and non-institutional corrections that deal with detainees and sentenced prisoners. The Bureau of Corrections (BuCor) has begun implementing the so-called Mandela rule, which categorizes convicts as “persons deprived of liberty” (PDL). They are in charge of sentenced prisoners with a prison term ranging from three years and one day and above with their programs in rehabilitating and reforming PDLs in preparation for their return to mainstream society. In the Province of Cagayan, it has three (3) district jails with a total of Four Hundred Eighty Seven (487) Persons Deprived of Liberty (PDLs) in their custody. This study was limited on the categorization of Persons Deprived of Liberty (PDLs) in the province of Cagayan, particularly the three district jails: the Aparri, Tuao, and Tuguegarao City. The researcher made use of a questionnaire to gather the needed data from the respondents. An interview was also conducted in order to verify some vague answers on the questionnaire. Findings of the study on age: most of the respondents percentages belong to the age brackets of 18-27 for Aparri District Jail, while 22 or 34.37 percent belong to the age brackets of 38-47 for Tuao District Jail and 102 or 32.27 percent belong to the age brackets of 28-77 for Tuguegarao City District Jail. The lowest frequency of 2 or .63 percent belongs to the bracket of below 18 years of age; the majority are males, married, Roman Catholic, reached/finished high school, self-employed, committed crimes against special laws and were arraigned, attended 1-5 times court hearings, been in jail for almost 1 month - 6 months, and most claimed that they were alleged suspects of the crimes charged against them. It is therefore concluded that select variables like highest educational attainment and occupation before detention of the respondents have something to do with the commission of crimes.